PENGARUH KETERAMPILAN MENGAJAR YANG DIMILIKI MAHASISWA DAN SELF-ESTEEM TERHADAP MINAT SERTA IMPLIKASINYA PADA KESIAPAN MENJADI GURU (Survey Pada Mahasiswa Angkatan 2020 di Pendidikan Ekonomi Universitas Siliwangi) - Fitriya Fitriya; Rendra Gumilar; Ai Nur Solihat (JURNAL ILMIAH NUSANTARA, 2024)
This research discusses the readiness to become a teacher that must be formed from college, through choosing an education major that suits your talents and interests, in order to prepare for a career as an educator. This research aims to examine the influence of students' teaching skills and self-esteem on their interests and implications for readiness to become teachers. Survey of economic education students class of 2020. The research method used is quantitative research. Implemented and supported by survey design using an explanatory survey approach. The sample in this study was non-probability sampling with a total of 110 students. The data analysis technique used is path analysis. The results of the path analysis obtained the regression equation Y = 0.195 X1 + 0.000 X2 +0.748 e1 and Z = 0.049 The results of the path analysis show that there is a direct influence between the Teaching Skills and Self-Esteem variables on Interest, the Self-Esteem variable on Readiness to Become a Teacher. And there is an indirect influence between the Teaching Skills variable on Readiness to Become a Teacher.